Erratum to: In-use Stability of Hydrocortisone Injection Preparations at a Regional Referral Hospital in Central Java - Erza Genatrika; Elza Sundhani; Eka Fitri Adriana; Ni Made Dharma Shantini Suena (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Erratum to: Jurnal Ilmiah Medicamento 2025; 11(2): 185-192 DOI original article: https://doi.org/10.36733/medicamento.v11i2.11538 After the publication of this article, errors were identified in the in-text citation, in Tables 2, 3, and 4, and in the reference list. The publisher wishes to apologize for any inconvenience this may have caused.